Nasal delivery of neurotherapeutics via nanocarriers: Facets, aspects, and prospects - Rajput, Amarjitsing; Pingale, Prashant; Dhapte-Pawar, Vividha (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD) is one of the neurological ailments which continue to represent a major public health challenge, owing to increased life expectancy and aging population. Progressive memory loss and decrease in cognitive behavior, owing to irreversible destruction of neurons along with expensive therapeutic interventions, call for an effective, alternate, yet affordable treatment for Alzheimer’s disease. Safe and effective delivery of neurotherapeutics in Alzheimer’s like central nervous system (CNS) disorders still remains elusive despite the major advances in both neuroscience and drug delivery research. The blood–brain barrier (BBB) with its tight endothelial cell layer surrounded by astrocyte foot processes poses as a major barrier for the entry of drugs into the brain. Nasal drug delivery has emerged as a reliable method to bypass this blood–brain barrier and deliver a wide range of neurotherapeutic agents to the brain effectively. This nasal route comprises the olfactory or trigeminal nerves originating from the brain and terminating into the nasal cavity at the respiratory epithelium or olfactory neuroepithelium. They represent the most direct method of noninvasive entry into the brain, opening the most suitable therapeutic avenue for treatment of neurological diseases. Also, drugs loaded into nanocarriers can have better interaction with the mucosa that assists in the direct brain delivery of active molecules bypassing the BBB and achieving rapid cerebrospinal fluid levels. Lipid particulate systems, emulsion-based systems, vesicular drug delivery systems, and other nanocarriers have evolved as promising drug delivery approaches for the effective brain delivery of anti-Alzheimer’s drugs with improved permeability and bioavailability via the nasal route. Charge, size, nature of neurotherapeutics, and formulation excipients influence the effective and targeted drug delivery using nanocarriers via the nasal route. This article elaborates on the recent advances in nanocarrier-based nasal drug delivery systems for the direct and effective brain delivery of the neurotherapeutic molecules. Additionally, we have attempted to highlight various experimental strategies, underlying mechanisms in the pathogenesis and therapy of central nervous system diseases, computational approaches, and clinical investigations pursued so far to attain and enhance the direct delivery of therapeutic agents to the brain via the nose-to-brain route, using nanocarriers.